Can retro-reflective materials replace diffuse highly reflective materials for urban buildings' wall to improve outdoor thermal comfort?. Issue 4 (April 2023) - Yuan, Jihui; Shimazaki, Yasuhiro; Zhang, Ruijun; Masuko, Shingo; Cao, Shi-Jie
Abstract: In recent years, there have been numerous studies on the application of retroreflective (RR) materials to exterior building walls to relieve the urban heat island (UHI) phenomenon and save building energy consumption instead of diffuse highly reflective (DHR) materials. Experimental measurements were undertaken to investigate the impact of applying DHR and RR materials to building exterior walls on the outdoor thermal environment. DHR and RR walls were tested with three canyon aspect ratios ( H / D ) of 0.5, 1.0, and 1.5, respectively, with seven environmental indexes recorded and compared, including air temperature ( T a ), relative humidity ( R H ), sol-air temperature ( S A T ), operative temperature ( O T ), standard effective temperature ( S E T * ), change in operative temperature ( C O T ), and real-time solar reflectance ( ρ ). The results show that the RR wall is more effective in improving the outdoor thermal environment, where S A T decreased by 4.5 °C, S E T * decreased by 0.5 °C, and COT decreased by 1.2 °C, on average, while it can also improve the real-time solar reflectance ( ρ ) by 12% on average compared to the DHR wall. Moreover, it gets more effective in scenarios with a higher canyon aspect ratio. Graphical abstract: Image 1 Highlights: Wall-model experiments indicate that retroreflective wall is more efficient in improving outdoor thermal environment than DHR wall. Results show that the higher the urban aspect ratio, the better the impact of retroreflective wall on the outdoor thermal environment. Results show that the real-time solar reflectance of retroreflective wall is larger than that of diffuse highly reflective wall in large urban aspect ratio. RetroReflective materials with similar solar reflectivity to diffuse highly reflective materials can improve outdoor thermal environment and reduce urban heat island effect. Abstract : Urban heat island; RR material; DHR material; Thermal environment index; Wall-model experiment.